METHODOLOGICAL APPROACHES AND TACTICAL TECHNIQUES FOR THE USE OF SHORT-BARRELED WEAPONS IN MODERN COMBAT - Popov, Serhii; Cherkashyn, Serhii; Cherkashyn, Oleksandr (Honor and Law, 2025)
The article examines tactical techniques and methodological approaches to the use of short-barreled weapons in modern combat. Emphasis is placed on their use in close fire contact and dynamic combat situations. The relevance of the topic is due to the intensity of combat operations in dense urban areas and confined spaces, where the use of such weapons is of particular importance. The tactical techniques and methods of using short-barreled weapons in real combat conditions have been systematized and analyzed. The analysis showed that, thanks to their compactness and quick deployment, short-barreled weapons are an effective tool in close combat. In conditions of increased stress on the shooter, key techniques such as instinctive shooting and quick transition to a backup weapon are critical.